2017
DOI: 10.1038/s41598-017-10810-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards large-scale in free-standing graphene and N-graphene sheets

Abstract: One of the greatest challenges in the commercialization of graphene and derivatives is production of high quality material in bulk quantities at low price and in a reproducible manner. The very limited control, or even lack of, over the synthesis process is one of the main problems of conventional approaches. Herein, we present a microwave plasma-enabled scalable route for continuous, large-scale fabrication of free-standing graphene and nitrogen doped graphene sheets. The method’s crucial advantage relies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 72 publications
(100 reference statements)
2
61
0
Order By: Relevance
“…In the present work, in-situ direct synthesis of free-standing N-graphene flakes at a relatively high yield (~ 1.3 mg min −1 ), was achieved in a single step by employing microwave plasma (see supplementary material) operating at atmospheric pressure conditions 40 44 . An ethanolic solution of ammonia (4 wt %) was used as precursor of both carbon and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, in-situ direct synthesis of free-standing N-graphene flakes at a relatively high yield (~ 1.3 mg min −1 ), was achieved in a single step by employing microwave plasma (see supplementary material) operating at atmospheric pressure conditions 40 44 . An ethanolic solution of ammonia (4 wt %) was used as precursor of both carbon and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma properties have been tailored to achieve selective synthesis of free-standing N-graphene sheets. The flowing sheets were submitted to UV and IR irradiation in the post-plasma zone during their flight to the collecting system to further improve their structural quality 40 . Raman spectroscopy, SEM and TEM and XPS were used to characterize the morphology, microstructure and chemical properties of the synthesized material.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectra of the remaining three samples, the red peak at about 284.8 eV is attributed to graphitic sp 2 carbon [19,20,47,49]. The peaks around 285.4 and 287.1 eV are attributed to C-O and C=O respectively, and the very broad peak around 290 eV is the result of the sp 2 carbon π→π * 'shake-up' satellite [50].…”
Section: Resultsmentioning
confidence: 96%
“…25 Since this discovery, plasma reactors with different designs have been utilized to create GSG. [27][28][29][30][31]35,[41][42][43] For example, GSG can be produced through the delivery of ethanol into surface wave-induced microwave plasmas at atmospheric conditions 28,29,31 [44][45][46][47] can also generate atmospheric pressure Ar plasmas that are capable of creating GSG. 27 A TIAGO consists of a waveguide whose central section is reduced in height [ Fig.…”
Section: Factors That Influence Graphene Synthesis In Atmospherimentioning
confidence: 99%
“…The morphology of crumpled graphene has been compared with that of crumpled paper. 43,52 However, GSG may be crumpled because of the presence of graphitic nanocrystals in the synthesized sheets. 71 In situ TEM has revealed that graphitic nanocrystals provide GSG with additional mechanical stability, enable the material to reversibly deform, and prevent GSG from being flattened like paper.…”
Section: Graphitic Nanocrystals For Lubricationmentioning
confidence: 99%